Electric field vector measurements in a surface ionization wave discharge. (15th September 2015) - Goldberg, Benjamin M; Böhm, Patrick S; Czarnetzki, Uwe; Adamovich, Igor V; Lempert, Walter R
Abstract: This work presents the results of time-resolved electric field vector measurements in a short pulse duration (60 ns full width at half maximum), surface ionization wave discharge in hydrogen using a picosecond four-wave mixing technique. Electric field vector components are measured separately, using pump and Stokes beams linearly polarized in the horizontal and vertical planes, and a polarizer placed in front of the infrared detector. The time-resolved electric field vector is measured at three different locations across the discharge gap, and for three different heights above the alumina ceramic dielectric surface, 100, 600, and 1100 μ m (total of nine different locations). The results show that after breakdown, the discharge develops as an ionization wave propagating along the dielectric surface at an average speed of 1 mm ns −1 . The surface ionization wave forms near the high voltage electrode, close to the dielectric surface ( 100 μ m). The wave front is characterized by significant overshoot of both vertical and horizontal electric field vector components. Behind the wave front, the vertical field component is rapidly reduced. As the wave propagates along the dielectric surface, it also extends further away from the dielectric surface, up to 1 mm near the grounded electrode. The horizontal field component behind the wave front remains quite significant, to sustain the electron current toward the high voltage electrode. After the wave reaches the grounded electrode, the horizontal field component experiences a secondary rise in the quasi-dc discharge, where it sustains the current along the near-surface plasma sheet. The measurement results indicate presence of a cathode layer formed near the grounded electrode with significant cathode voltage fall, ≈3 kV, due to high current density in the discharge. The peak reduced electric field in the surface ionization wave is 85–95 Td, consistent with dc breakdown field estimated from the Paschen curve for hydrogen. The present set of data on electric field distribution in a surface ionization wave discharge provides an experimental reference for validation of kinetic models and assessing their predictive capability.